Context of biethnic acceptance, biethnic affirmation, and life satisfaction among Korean biethnic adolescents. (23rd March 2020) - Chung, Grace H.; Lee, Jiyeon; Gonzales‐Backen, Melinda
ABSTRACT: Introduction: This study aimed to identify latent profiles based on familial ethnic socialization, peer discrimination, and school multicultural climate among biethnic adolescents in South Korea and to examine how the emerged profiles were related to their life satisfaction.We also examined how biethnic affirmation interacted with the profiles in predicting life satisfaction. Methods: Questionnaire data from the first wave of the Panel Survey of Korean Multicultural Youth Adjustment was used. The sample consisted of 358 biethnic adolescents in 5th and 6th grade in South Korea. The meanage was 11.41 years old. Approximately 60% of the participants were in 5th grade and 51.68% were girls. Results: The results of LPA showed that familial ethnic socialization, peer discrimination, and school multicultural climate formed two distinct profiles in the current sample. These profiles were characterized as contexts of high and low biethnic acceptance. Biethnic adolescents in the context of high biethnic acceptance were significantly more satisfied with their lives than those in the context of low biethnic acceptance.Further, the positive association between biethnic iaffirmation and life satisfaction was more pronounced among adolescents in the context of low biethnic acceptance. Conclusions: Findings suggest the importance of promoting biethnic acceptance across family, peer, and school settings for adolescents' biethnic affirmation and life satisfaction.